Safety and efficacy of general anesthesia versus spinal anesthesia in percutaneous nephrolithotomy - Srinivasa VY; Kailash P Dev; Anjali Kumari B (Asian Journal of Medical Sciences, 2024)
Background: Percutaneous nephrolithotomy (PCNL) is the preferred treatment for the removal of large kidney stones, sized >20 mm. However, there is still an ongoing debate concerning the best anesthesia for PCNL.Aims and Objectives: The objective of this study was to assess and compare the efficacy and safety of spinal anesthesia (SA) versus general anesthesia (GA) in PCNL.Materials and Methods: A prospective randomized study included eighty-two patients who were enrolled to receive either SA or GA for PCNL. The study assessed patients’ characteristics, vital parameters, requirements for additional analgesia, and patient satisfaction. In addition, intraoperative and post-operative complications were documented. Patients’ satisfaction was also analyzed.Results: In both groups, the vital parameters were consistently maintained at safe levels during the procedures. Patients in the SA group exhibited a lower analgesia consumption on the 1st post-operative day compared to the GA group (P